2018
DOI: 10.1136/annrheumdis-2017-212658
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase Fyn promotes osteoarthritis by activating the β-catenin pathway

Abstract: Fyn accumulates and activates β-catenin signalling in chondrocytes, accelerating the degradation of the articular cartilage and OA development. Targeting Fyn is a novel and potentially therapeutic approach to the treatment of OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 32 publications
5
49
0
Order By: Relevance
“…the pathogenesis of OA by inducing the chondrocyte anabolic and catabolic imbalance, including the downregulation of Collagen II and Aggrecan, as well as the upregulation of ADAMTS-5 and MMP-13 [45][46][47]. Therefore, we treated chondrocytes with IL-1b to simulate the OA microenvironment in vitro, similar to other studies [10,48]. When chondrocytes were exposed to IL-1b, we observed the same SGK1 expression pattern as detected in OA cartilage.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…the pathogenesis of OA by inducing the chondrocyte anabolic and catabolic imbalance, including the downregulation of Collagen II and Aggrecan, as well as the upregulation of ADAMTS-5 and MMP-13 [45][46][47]. Therefore, we treated chondrocytes with IL-1b to simulate the OA microenvironment in vitro, similar to other studies [10,48]. When chondrocytes were exposed to IL-1b, we observed the same SGK1 expression pattern as detected in OA cartilage.…”
Section: Discussionsupporting
confidence: 71%
“…Among these pro‐inflammatory cytokines, increased IL‐1β levels have consistently been observed in the cartilage tissue, synovial fluid and the blood of patients with OA , and it plays a critical role in the pathogenesis of OA by inducing the chondrocyte anabolic and catabolic imbalance, including the downregulation of Collagen II and Aggrecan, as well as the upregulation of ADAMTS‐5 and MMP‐13 . Therefore, we treated chondrocytes with IL‐1β to simulate the OA microenvironment in vitro , similar to other studies . When chondrocytes were exposed to IL‐1β, we observed the same SGK1 expression pattern as detected in OA cartilage.…”
Section: Discussionsupporting
confidence: 69%
“…Mouse primary chondrocytes were collected from the knee cartilage of new-born C57BL/6 mice as described previously ( Li et al, 2018 ). Articular cartilage derived from the knee joints was dissected into pieces in sterilized phosphate-buffered saline (PBS) and digested with 0.25% trypsin at 37°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Further comparison with published ageing or osteoarthritis-regulated cartilage proteomic studies [15][16][17][18][19][20][21][22] revealed a list of 34 rhythmic proteins being dysregulated in disease condition and/or in aging (Table 1).…”
Section: Figure 2 Protein Interaction Network Of Rhythmic Proteins Smentioning
confidence: 99%